Otoritas Ilmuan Sosial Politik dalam Dinamika Politik - Muhammad Kausar Bailusy (The Politics : Jurnal Magister Ilmu Politik Universitas Hasanuddin, 2015)
Abstract: The student world needs to be understood is the embryo of scientists in various fields of science. Fields that are being elaborated at this point that social science and political science, as an object of socio-political student who run and run to achieve a degree of social science and political science. Formal constitutional conditions recognize the ownership of knowledge by students to be bachelor or called social and political scientists spontaneously have political authority. Political scientist who studies the authorities are interacting in a political system that is filled with political dynamics. The results can be inferred from this idea that new students accepted in the field of social and political should focus on the smart thinking and gain the knowledge from social and political sciences. Current conditions the bachelor and scientists from social and political sciences is needed in line with the dynamics of the political system. Therefore, at the present time as a new student should be able to understand the socio-political academic demonstrations and acts as an intelligent student in demonstrating that build on the idea as a contribution to the government. At that moment the embryo of political social scientists should be build within students as prospective scientists with rational and objective view.Keywrods: Scientist, Bachelor, Social Politics, Political DynamicAbstrak: Perlu dimaknai dunia kemahasiswaan adalah embrio ilmuan dalam berbagai bidang keilmuan. Bidang yang sedang ditekuni pada saat ini yakni ilmu sosial dan ilmu politik, sebagai objek mahasiswa sospol yang bergayuh dan terus bergayuh untuk mencapai gelar ilmu sosial dan ilmu politik. Kondisi formal konstitusional mengakui kepemilikan ilmu oleh mahasiswa menjadi sarjana atau disebut ilmuan sosial politik dan spontan memiliki otoritas ilmuan sosial politik. Kajian otoritas ilmuan politik yang sedang berinteraksi dalam sistem politik yang penuh dengan dinamika politik. Hasil yang dapat disimpulkan dari gagasan ini yakni mahasiswa baru yang diterima dalam bidang sosial dan politik harus memfokuskan cara berpikir untuk cerdas dan meraih kemenangan dalam menuntut ilmu sosial dan politik. Kondisi sekarang para sarjana atau ilmuan sosial politik sangat dibutuhkan seiring dengan dinamika sistem politik. Oleh sebab itu pada saat sekarang sebagai mahasiswa baru sosial politik harus mampu memahami demonstrasi secara akademik dan bertindak sebagai mahasiswa yang cerdas dalam berdemonstrasi yakni membangun ide sebagai kontribusi pada pemerintah. Pada saat itulah titian embrio ilmuan sosial politik terbangun dalam diri mahasiswa sebagai calon ilmuan yang rasional dan objektif.Kata Kunci: Ilmuan, Sarjana, Sosial Politik, Dinamika Politik